EXCHANGE RATE DETERMINATION IN HIGH FRAGILE EMERGING COUNTRIES - Okyay Ucan; Cemil Serhat Akin; Cengiz Aytun (European Scientific Journal, ESJ, 2014)
There exist exchange rate determination problem together with removing the restrictions on financial capital movements after 1970’s. In the economics literature various type of models that are purchasing power parity, Mundell Fleming Model, Sticky Price Monetary Approach, Flexible Price Monetary Approach and Hibrit Model are explicated and tested for countries’ economies. There may be more threats for the high fragile emerging countries. Argentina, Russia and Chile are included to the “fragile five” countries i.e. Turkey, Brazil, India, Indonesia and South Africa. Central Bank of USA (FED) announced to reduce the bond purchases and applied this issue gradually. Mostly emerging countries but also others suffer damage to their economies because of this argument. In this study the fragile countries that are mentioned above are examined whether their exchange rates behave like one of the determination model in the 1980-2011 periods. Our hypothesis is these countries behave like Flexible Price or Sticky Price Monetary Model consistent with the literature. Unit root test and cointegration are used to test the hypothesis.